Security Cballenges Facing Our Country and Countermeasure Recommendations Under New Network Security Tbreats - Mingjie Ma; Fenggang Sun; Lidong Zhai; Yuejin Du (Dianxin kexue)
With the development of the internet and peripheral network products, information security draw more and more attention, after the outbreak of the prism, the national information security is not only caused the attention of world leaders, has attracted wide attention from people around the world. The security challenges in the new network security threats which our country was facing were analyzed and recommendations for future network development in China in the field of information security were put forward.